Determinants of Ride-Hailing Adoption: Extending TAM with Trust, Service Quality, and Gamification - Nik Azman, Nik Hadiyan; Setiawaty, Aswanti; Salehati, Nurun Ala; Ramayanti, Rizka (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
This study examines the determinants of Gojek ride-hailing adoption in Indonesia by extending the Technology Acceptance Model. The model integrates perceived usefulness, perceived ease of use, trust, service quality, and gamification as antecedents of adoption in an emerging-market context. A cross-sectional survey of 100 active Gojek users was conducted using convenience sampling. Each construct was measured with four items on a five-point Likert scale. Partial Least Squares–SEM (SmartPLS 4) was used in this study. Perceived usefulness and gamification significantly and positively predict adoption, while perceived ease of use, service quality, and trust show no significant direct effects (p > 0.05). The model explains 64.9% of the variance in adoption (R² = 0.649) and demonstrates strong predictive relevance (Q² = 0.600). Findings underscore the primacy of utilitarian value and gamified design features in driving ride-hailing adoption